Schools of the RSFSR North-West under Occupation of 1941-1944 - Krasnozhenova, Elena E.; Vycherov, Dmitry A. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
The authors analyze the Nazi occupation policy in the field of education in the north-west of the RSFSR. The work is based on the documents from central and regional archives (the State Archive of the Russian Federation, the Central State Archive of Historical and Political Documents of St. Petersburg, the Central State Archive of St. Petersburg). The authors used the documents and materials of the Extraordinary State Commission for the Establishment and Investigation of the Atrocities of the German Fascist Invaders and Their Accomplices, as well as clerical documents of the partisans and documents related to the activities of the occupation administration in the field of school education. Among the sources used are the documents and memoirs published in various collections. The author within their work shows: the reduction in the number of schools and students in the region, changes in the content of curricula, the measures of the occupying authorities towards teaching staff, and the problems of organizing the educational process. The authors note that the Nazi occupation policy in the field of school education was aimed at eradicating the Soviet ideology from the educational process, establishing total control over the younger generation, as well as educating children and adolescents as workers for Germany. The authors conclude that it was not possible to establish a full-fledged educational process in the north-west of Russia under occupation for many reasons: the large amount of left-out of students, the actions of partisans, a lack of teaching staff, educational literature and school supplies, and few appropriate premises. In those years children and adolescents suffered from hunger, deprivation, and deaths of relatives; many of them had no opportunity to attend school.